Generation of a cancer testis antigen mCherry reporter HCT116 colorectal carcinoma cell line. Issue 10 (October 2018) - Chhetri, Jyoti B.; Drousioti, Elena; Guerra-Assunção, José Afonso; Herrero, Javier; Ooi, Steen K.T.
Abstract: In the context of cancer immunotherapy, agents that target the immune system to cancer cells need to fulfil two criteria: 1) that they are only expressed on the desired target cell and 2) that they can elicit a potent immunological response. Cancer Testis Antigens are a large disparate family of factors ordinarily expressed in the germ-line but aberrantly expressed across multiple types of cancer. The ability to enforce their expression on tumour cells is an attractive strategy that could render such cells potent targets of the immune system, but very little is known about their regulation. We describe the generation of an mCherry reporter cell line using HCT116 colorectal carcinoma cells that we anticipate will be useful for screen-based approaches to identify novel regulators of CTA expression. Discoveries arising from their use could in future be exploited to enhance tumour cell immunogenicity and improve cancer immuno-therapy.